Correlation analysis between the pulmonary function test and the radiological parameters of the main right thoracic curve in adolescent idiopathic scoliosis - Yonggang Wang; Fengguang Yang; Dongmin Wang; Haiyan Zhao; Zhanjun Ma; Peifen Ma; Xuchang Hu; Shixiong Wang; Xuewen Kang; Bingren Gao (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Scoliosis causes thoracic deformities, and it is necessary to assess these changes in pulmonary function test (PFT). To determine how measurements of spinal and thoracic cage deformities are related to pulmonary function. Methods Seventy-two patients with main right thoracic curvature in adolescent idiopathic scoliosis (AIS) underwent a PFT and a radiological parameter evaluation of spinal and thoracic cage deformities. Simple and multiple linear regressions were also used to note whether a combination of variables might better predict PFT values. Means were compared using the two-sample t test or one-way ANOVA with Tukey’s multiple comparison methods. Results Forced vital capacity (FVC)% predicted had significantly negative correlations with main thoracic curve Cobb (MT-Cobb) (R 2 = 0.648, p < 0.001), main thoracic curve-rib hump (MT-RH) (R 2 = 0.522, p < 0.001), main thoracic curve apical vertebral body-to-rib ratio (MT-AVB-R) (R 2 = 0.536, p < 0.001), and main thoracic curve apical vertebra translation (MT-AVT) (R 2 = 0.383, p < 0.001). Multiple regression analysis was performed with FVC% predicted as the dependent variable and MT-Cobb, MT-RH, MT-AVB-R, and MT-AVT as the independent variables. MT-Cobb, MT-RH, MT-AVB-R, and MT-AVT were factors with a significant effect on FVC% predicted (p < 0.001). For 45 patients who had preoperative FVC impairment (FVC% predicted < 80%), their MT-Cobb averaged 76.71°. Twenty-seven patients with normal preoperative FVC (FVC% predicted ≥ 80%) had a smaller mean MT-Cobb of 52.03° (p < 0.001). In other radiological parameters, the impaired FVC group had a MT-AVT of 54.29 mm compared to 38.06 mm for the normal FVC group (p < 0.001). MT-AVB-R averaged 2.92 for the impaired FVC group and 1.78 for the normal FVC group (p < 0.001). MT-RH averaged 28.79 mm for the impaired group and 16.62 mm for the normal group (p < 0.001). Further stratification of preoperative PFT results is divided into three groups. The three groups also showed significant differences in MT-Cobb, MT-RH, MT-AVB-R, and MT-AVT (p < 0.001). Conclusion Severe scoliosis leads to an increased degree of thoracic deformity, which increases the risk of lung damage in AIS. Moreover, a more accurate assessment of pulmonary function is achieved through radiological parameters and PFTs.